2000
DOI: 10.1093/jnci/92.16.1321
|View full text |Cite
|
Sign up to set email alerts
|

Decision Framework for Chemotherapeutic Interventions for Metastatic Non-Small-Cell Lung Cancer

Abstract: This decision framework allows the comparison of different treatment regimens based on various cost-effectiveness thresholds. Our analysis also supports the use of chemotherapy regimens and the abandonment of best supportive care as the standard of care for patients with advanced NSCLC. [J Natl Cancer Inst 2000;92:1321-9].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…This CUA of chemotherapy for metastatic NSCLC applied a decision-analysis model on a hypothetical cohort of lung cancer patients. The analysis used mean utility estimates provided by a survey amongst oncologists [3]. No other CUA alongside cancer clinical trials has as yet been reported on chemotherapy for advanced-stage NSCLC, which is probably related to the fact that the reported differences in QoL between platinum doublets only show discrete differences at best [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This CUA of chemotherapy for metastatic NSCLC applied a decision-analysis model on a hypothetical cohort of lung cancer patients. The analysis used mean utility estimates provided by a survey amongst oncologists [3]. No other CUA alongside cancer clinical trials has as yet been reported on chemotherapy for advanced-stage NSCLC, which is probably related to the fact that the reported differences in QoL between platinum doublets only show discrete differences at best [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In the last step, these utilities were combined with the survival data from the randomised study in order to obtain QALYs. For the baseline calculation, the average utilities were multiplied by the LYS, an approach also used by BERTHELOT et al [3] For the sensitivity analyses, the QALYs were calculated from the area under the utility curve for the 24-week treatment period by making a summation of the utility per week.…”
Section: Survival and Cost-effectivenessmentioning
confidence: 99%
“…A cost-benefit analysis supports the use of chemotherapy regimens and the abandonment of best supportive care as the standard of care for patients with advanced NSCLC [61].…”
Section: Comparison Of New Protocolsmentioning
confidence: 97%
“…In fact there have been no empirical studies that have tried to elicit utilities directly for NSCLC patients undergoing PET tests. Those employed by the HTBS model were taken from earlier reports by Berthelot et al [9] and Marshall et al [10] using estimates made by oncologists rather than from patients themselves.…”
Section: Objectivesmentioning
confidence: 99%